Ultrasound assisted extraction of the polysaccharide from Tuber aestivum and its in vitro anti-hyperglycemic activity. (October 2019) - Mudliyar, Devshri S.; Wallenius, Janne H.; Bedade, Dattatray K.; Singhal, Rekha S.; Madi, Nuri; Shamekh, Salem S.
Abstract: Tuber aestivum is one of the most popular and delicious truffles in the world economic market and is reported to possess a wide range of biological activities. The total carbohydrate of this truffle constitutes about 5.65% w/w dry weight basis (dwb). The present work compares the yield of the polysaccharide obtained by conventional hot water extraction followed by alcohol precipitation, and ultrasound assisted extraction using low power 150 W probe sonifier. The parameters of ultrasound assisted extraction (amplitude, extraction time, pH, and liquid-solid ratio) from the fruiting body of T. aestivum were optimized using Taguchi orthogonal array and central composite design. The optimal parameters of extraction were a liquid-solid ratio of 75:1 for 15 min at pH 6.5 at an amplitude of 25%, which yielded 68.91 ± 1.54% w/w dwb polysaccharide. The FTIR and SEM characteristics of the polysaccharides obtained by ultrasonic extraction and conventional hot water extraction were similar. Further, the polysaccharides extracted from T. aestivum demonstrated a significant in vitro anti-hyperglycemic activity. Highlights: Polysaccharide from Tuber aestivum was extracted using low power probe sonicator. The maximum extraction yield of the polysaccharide was 68.91 ± 1.54% (w/w dwb). A liquid: solid ratio of 75 at pH 6.5 for 15 min and an amplitude of 25% was optimum. FTIR and SEM of ultrasound and hot water extracted polysaccharides were similar. The polysaccharides showed considerable in vitro anti-hyperglycaemic activity.